Has Management Studies Lost Its Way? Ideas for More Imaginative and Innovative Research - Alvesson, Mats; Sandberg, Jörgen (Journal of Management Studies, 2013)
abstractDespite the huge increase in the number of management articles published during the three last decades, there is a serious shortage of high‐impact research in management studies. We contend that a primary reason behind this paradoxical shortage is the near total dominance of incremental gap‐spotting research in management. This domination is even more paradoxical as it is well known that gap‐spotting rarely leads to influential theories. We identify three broad and interacting key drivers behind this double paradox: institutional conditions, professional norms, and researchers' identity constructions. We discuss how specific changes in these drivers can reduce the shortage of influential management theories. We also point to two methodologies that may encourage and facilitate more innovative and imaginative research and revisions of academic norms and identities.